Z-scheme NiFe LDH/Bi4O5I2 heterojunction for photo-Fenton oxidation of tetracycline - Zhu, Chenxi; Wang, Yingjun; Qiu, Longyu; Yang, Weiwei; Yu, Yongsheng; Li, Jiaming; Liu, Yequn (Journal of alloys and compounds, 2023)
Designing an efficient catalyst for photo-Fenton organic contaminant degradation has been an important subject intended to solve the related environmental deterioration and enormous energy crises. However, the rapid cycle of Fe3+/Fe2+ in a wide pH range based on photo-Fenton reaction is still challenging. Here, we prepare highly effective and stable Z-scheme NiFe LDH/Bi4O5I2 heterogeneous Fenton catalyst for tetracycline (TC) photodegradation. The optimized NiFe LDH/Bi4O5I2 composite (NFBOI-35) reaches more than 95% TC degradation efficiency in Fenton system under visible light irradiation. Excellent stability, low metal ions leaching concentration and wide pH applicability distinguish make NFBOI-35 be a potential candidate for TC elimination. The improved photo-Fenton performance is mainly attributed to the construction of Z-scheme heterojunction and the accelerated decomposition of H2O2, which realizes the remarkable synergy effect between photocatalysis and Fenton reaction. This work would be beneficial to design Z-scheme catalyst for photo-Fenton organic contaminants degradation and other solar energy application. [Display omitted] •A novel Z-scheme NiFe LDH/Bi4O5I2 composite was prepared as Fenton photocatalyst.•The optimal composite (NFBOI-35) achieves over 95% tetracycline degradation ability.•Superior photocatalytic activity results from efficient carrier separation.•The NFBOI-35 photo-Fenton system displays broad pH applicability.